Überlegungen zu einer verhaltenswissenschaftlich fundierten Kapitalmarktforschung (Teil I) - Michael Bitz; Andreas Oehler (Kredit und Kapital, 1993)
The second part of the article deals with the second group of determinants of private investor behavior, the person of the investor himself. The considerations differentiate between determinants of the personal disposition like emotional, motivational or cognitive determinants (e. g. the degree to which a private investor is influenced by others) and the personal situation described by sociodemographic (e.g. age, sex) and socioeconomic characteristics (e.g. income, wealth, life cycle, profession). The conceptual considerations are illustrated by some more 1992 survey results.
Keywords: 330